Tackling Terrorism in Africa: Post-9/11 US Security Policies and Radicalisation in Kenya - Papale, Simone (2021)
Since the beginning of the war on terror, the US has intensified security efforts in Africa, promoting regional initiatives and increasing bilateral cooperation with local governments to fight terrorism on the ground. Yet, despite Washington’s attempts, Islamist violence on the continent is on the rise. What is more, several of US African partners have been criticised for overstepping legal boundaries in the conduct of counter-terrorism operations, committing human rights violations against African people. This study fills a longstanding gap in the literature by exploring whether, and above all, how post-9/11 US security policies may have a negative impact on radicalisation in African states, increasing dynamics culminating with mobilisation into terrorism. Relying on a critical theoryinspired research orientation, it sets up an innovative and interdisciplinary framework, shifting the emphasis to local politics as a determinant for the impact of US policies and pointing to dynamics of violent interaction between African states and their population as a crucial dimension of radicalisation. Incorporating analytical elements from the research on remote warfare, security assistance and the role of agency, and social movements, the proposed framework develops around a three-step causal mechanism hypothesised to connect US policies to the increase in radicalisation on the ground. The mechanism posits that post-9/11 US security policies have a negative impact in African states characterised by the threat of terrorism and the use of indiscriminate repression against suspect groups by: 1) leading to the establishment of a partnership relationship within the framework of remote warfare; 2) from the partnership relationship, African states gain resources and room for manoeuvre to implement indiscriminate repression; 3) indiscriminate repression causes an increase in radicalisation in African states. To test such a mechanism, the research is designed as a case study, focusing on post-9/11 US security policies in Kenya by using theory-testing process tracing to identify the case-specific manifestations of the three steps. The research provides extensive evidence in support of the hypothesised mechanism in the case of Kenya, showing how US remote intervention, based on the provision of indirect support, has inadvertently contributed to fuelling the repressive campaign conducted by local security authorities against Muslims and ethnic Somalis, pushing the latter into the hands of the terrorist group Al Shabaab. Such findings have significant implications, pointing to the need of context-sensitive security policies acknowledging the political drivers of terrorism and the limits of remote warfare in Kenya. At the same time, they make a theoretical contribution, setting the foundation for a more thorough approach towards the study of US efforts in Africa which, by overcoming divisions in the discipline, could help shape more sustainable and effective security policies.